2011
DOI: 10.1152/japplphysiol.00267.2011
|View full text |Cite
|
Sign up to set email alerts
|

Airflow pattern complexity and airway obstruction in asthma

Abstract: The scientific and clinical value of a measure of complexity is potentially enormous because complexity appears to be lost in the presence of illness. The authors examined the effect of elevated airway obstruction on the complexity of the airflow (Q) pattern of asthmatic patients analyzing the airflow approximate entropy (ApEnQ). This study involved 11 healthy controls, 11 asthmatics with normal spirometric exams, and 40 asthmatics with mild (14), moderate (14), and severe (12) airway obstructions. A significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 57 publications
3
34
1
Order By: Relevance
“…This group of infants could be in need of diagnostic evaluation, which is only possible by long-term monitoring of lung function. Recordings of longer duration also enable the calculation of more robust measures of tidal airflow profiles than the conventional TBFV parameters, as well as complex indices of flow variability [38]. By using nocturnal recordings with IP, we demonstrated that preschool children with a high risk of asthma present with an increased variation of tidal flow profile shape, and momentarily lowered chaoticity, compared to children with a lower risk of asthma [14].…”
Section: Discussionmentioning
confidence: 89%
“…This group of infants could be in need of diagnostic evaluation, which is only possible by long-term monitoring of lung function. Recordings of longer duration also enable the calculation of more robust measures of tidal airflow profiles than the conventional TBFV parameters, as well as complex indices of flow variability [38]. By using nocturnal recordings with IP, we demonstrated that preschool children with a high risk of asthma present with an increased variation of tidal flow profile shape, and momentarily lowered chaoticity, compared to children with a lower risk of asthma [14].…”
Section: Discussionmentioning
confidence: 89%
“…Entropy measurements give a statistical probability that a series of points within a physiological signal will repeat themselves at a subsequent timepoint, within a given tolerance [13]. The entropy of FOT time series was recently investigated by VEIGA et al [14], who found that the entropy of airflow time series was reduced in patients with asthma compared with healthy controls, and that reduced entropy was associated with increased severity of airflow obstruction. However, the possible associations between the entropy of airway impedance measurements and other clinically important patient-centred outcomes in asthma, including asthma control and exacerbations, have not been evaluated.…”
mentioning
confidence: 99%
“…Therefore, interest in using fluctuation analysis to characterize respiratory patterns has become widespread over the past five years Veiga et al, 2011). Using these methods, Frey and colleagues (2005) investigated the use of the day-to-day fluctuations in peak expiratory flow (PEF) over 6 months in patients with chronic asthma to determine whether the future risk of exacerbation could be predicted from fluctuations in PEF.…”
Section: Contribution Of Forced Oscillation To Systems Medicine and Cmentioning
confidence: 99%